Evidence of existence of metastable SrFe12O19 nanoparticles - Martinez Garcia, Ricardo (2011)
The existence of metastable hexaferrite is reported. Synthesis of strontium hexaferrite, SrFe12O19, at 400 °C was realized under controlled oxygen atmosphere. Such technique allows obtaining of SrFe12O19 at lower temperatures than those by traditional methods (above 800 °C). Phase transformation occurred during a measurement of magnetization vs. temperature (heating up to 625 °C). The heat treatment induces a change from SrFe12O19 to γ-Fe2O3 (as the main phase), and SrFeO2.74 to Sr2Fe2O5. Together with these phase transformations, an increment in the amount of SrCO3 is detected. Magnetic study of the samples, before and after the heating, supports the structural analysis conclusions.